2022
DOI: 10.1136/bmjopen-2022-065825
|View full text |Cite
|
Sign up to set email alerts
|

Cohort profile: the Swedish Maternal Microbiome project (SweMaMi) – assessing the dynamic associations between the microbiome and maternal and neonatal adverse events

Abstract: PurposeThe Swedish Maternal Microbiome (SweMaMi) project was initiated to better understand the dynamics of the microbiome in pregnancy, with longitudinal microbiome sampling, shotgun metagenomics, extensive questionnaires and health registry linkage.ParticipantsPregnant women were recruited before the 20th gestational week during 2017–2021 in Sweden. In total, 5439 pregnancies (5193 unique women) were included. For 3973 pregnancies (73%), samples were provided at baseline, and for 3141 (58%) at all three time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…Furthermore, participants born outside of Sweden are underrepresented, possibly because of language barriers. However, in our recent cohort profile [13], we found that our cohort was fairly representative of the Swedish pregnant population.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Furthermore, participants born outside of Sweden are underrepresented, possibly because of language barriers. However, in our recent cohort profile [13], we found that our cohort was fairly representative of the Swedish pregnant population.…”
Section: Discussionmentioning
confidence: 67%
“…Here we use questionnaire data from the Swedish Maternal Microbiome (SweMaMi) cohort study [13] to identify potential risk factors for pre-pregnancy complications in comparison to having none.…”
Section: Aimmentioning
confidence: 99%
See 2 more Smart Citations
“…sex, gestational age, birth weight, multiple births, mode of delivery, first-time mothers, number of siblings, maternal age and BMI, gestational diabetes and hypertension, infections during pregnancy, and parental education and smoking (57)(58)(59)(60). It is gratifying that in MIAI the drop-out rate of 8% is low in comparison to other birth cohorts which also perform repeated collection of biomaterials, e.g., the SweMaMi cohort (59) and KUNO-Kids cohort (57) that recorded 40-50% of lost 1-year follow-ups. Hence, we assume that the MIAI cohort will be representative of an infant population in Central Europe.…”
Section: Discussionmentioning
confidence: 99%